UMBILICAL CORD BLOOD PH MEASUREMENT IN INTA-PARTUM PATHOLOGICAL CTG AND NEONATAL OUTCOMES (The Research of Medical Science Review, 2025)
Objectives: This study explores how umbilical cord blood pH levels relate to newborn health outcomes in cases where abnormal cardiotocography (CTG) patterns were observed during labor. Study Design: A prospective observational study. Place and Duration of Study: Conducted in the Neonatology Department at Shaikh Zayed Hospital, Lahore, for six months after ethical approval. Methodology: A total of 90 newborns with abnormal CTG patterns were included in the study using a non-probability consecutive sampling method. Immediately after birth, umbilical arterial blood was collected for pH analysis. Neonatal outcomes were evaluated based on Apgar scores, the need for mechanical ventilation, seizures, respiratory distress, sepsis, and mortality. The data was analyzed using SPSS version 21. Results: The average gestational age of the newborns was 37.5 ± 1.2 weeks, and the mean birth weight was 2.9 ± 0.4 kg. Among the 90 cases, 58 (64.4%) neonates had acidosis (pH < 7.2). Low Apgar scores were observed in 40% of neonates with acidosis compared to 15% in the non-acidotic group. NICU admissions were significantly higher among acidotic neonates (p = 0.003). The need for mechanical ventilation was also increased (35% vs. 10%, p = 0.002). Neonatal sepsis was reported in 18% of cases, while mortality was recorded in 8% of neonates with severe acidosis. Conclusion: This study indicates that umbilical cord blood pH is a reliable predictor of adverse neonatal outcomes. Routine umbilical pH screening in high-risk deliveries could enhance neonatal management and potentially reduce unnecessary NICU admissions.